CIRCULATING CELL-FREE DNA IS A BIOMARKER OF PREMATURE BIRTH AND COVID-19 AND PREDICTS PRENATAL CEREBRAL ISCHEMIA IN NEWBORNS - Komarevtseva, I.O.; Posternak, D.G.; Cherednichenko, R.V.; Shatrova, A.S.; Chernykh, Yu.A.; Balabanova, K.V.; Komarevtsev, V.N. (World of Medicine and Biology, 2022)
Circulating cell-free DNA is a possible marker of not only apoptosis, but also COVID-19 in pregnant, which can also be a trigger factor for premature birth and predicts prenatal hypoxic-ischemic encephalopathy injury in newborns. DNA fragmentation in tissues and blood plasma was measured with the diphenylamine assay. The material for the study was the peripheral blood from pregnant women and newborns, cord blood, tissue of the placenta. A comparison of the level of cfDNA in the serum of healthy pregnant and pregnant women with premature birth suggests a high level of it in women with premature birth. Pregnant women with COVID-19 had significantly higher cfDNA values as compared to those in healthy pregnant women in cord blood, placenta and in newborns from women with COVID-19. The level of cfDNA increased with the severity of neonatal hypoxic-ischemic encephalopathy injury in newborns from women with premature birth.